Production of probiotic garden cress (Lepidium Sativum) using Bifidobacterium Bifidum and its evaluation of nutritional value, biocontrol and growth rate ability - Golnaz Shambayati; Mojtaba Mohammadzadeh Vazifeh; Seyed Masoud Hosseini; Hasan Hajjami Barkousaraei (PLoS ONE, 2025)
Probiotics are one of the most beneficial elements in human health. Several studies have confirmed the health benefits of probiotics. The consumption of fermented vegetables is widespread worldwide and represents an important component of the human diet for a growing global population. In recent years, consumers have become more aware of the relationship between food and health, which has led to an increase in interest in functional foods. The global market for probiotic foods is growing rapidly due to the increasing consumer awareness. Although leafy vegetables are well-endowed with bacteria, including potentially probiotic strains of Lactobacillus, so far, plant-derived products have only been considered as carriers of probiotic cultures. This study aimed to produce probiotic garden cress using Bifidobacterium bifidum and to investigate its nutritional value, biocontrol, and growth rate and this is a great approach due to the increase in vegetarianism, lactose intolerance and people allergic to dairy products. Bifidobacterium bifidum (bb12) was inoculated into sterile cress seeds and the probiotic plant culture was done on days 0 and 3 after harvesting, in a TOS medium containing Mupirocin (MUP) antibiotic. The chemical properties (such as pH, acidity, and dry matter) of both samples were determined and the comparison of growth rate, fat content, vitamin C, and organoleptic properties was done. Bacterial survival in simulated gastrointestinal (SGI) conditions and its antifungal effect on Rhizoctonia solani were also analyzed. The number of bacteria on days 0 and 3 was 4×1013 and 2.3 ×1011 Colony Forming Unit/gram (CFU/g) respectively, which confirms the probiotic nature of the product (>106 bacteria). Also, significant difference (P≤0.05) was observed in the physicochemical parameters. Bacterial viability was reported as 6.3 ×1010 CFU/g in simulated gastric condition and as 3×106  CFU/g in simulated intestine condition, and the antifungal effect of Bifidobacterium on R. solani was 15%. It can be concluded that production of other probiotic vegetables might be possible and that the plant based probiotics can be used to support the growth of human intestinal bacteria and also maintain high cell viability during storage.